Building, Hosting and Recruiting: A Brief Introduction to Running Behavioral Experiments Online - Sauter, Marian; Draschkow, Dejan; Mack, Wolfgang (Brain sciences, 2020)
Researchers have ample reasons to take their experimental studies out of the lab and into the online wilderness. For some, it is out of necessity, due to an unforeseen laboratory closure or difficulties in recruiting on-site participants. Others want to benefit from the large and diverse online population. However, the transition from in-lab to online data acquisition is not trivial and might seem overwhelming at first. To facilitate this transition, we present an overview of actively maintained solutions for the critical components of successful online data acquisition: creating, hosting and recruiting. Our aim is to provide a brief introductory resource and discuss important considerations for researchers who are taking their first steps towards online experimentation.